(Un)Predictability and macroeconomic stability - Antonello D'Agostino; Domenico Giannone; Paolo Surico (European Central Bank (ECB), 2006)
This paper documents a new stylized fact of the greater macroeconomic stability of the U.S. economy over the last two decades. Using 131 monthly time series, three popular statistical methods and the forecasts of the Federal Reserve's Greenbook and the Survey of Professional Forecasters, we show that the ability to predict several measures of inflation and real activity declined remarkably, relative to naive forecasts, since the mid-1980s. This break down in forecast ability appears to be an inherent feature of the most recent period and thus represents a new challenge for competing explanations of the `Great Moderation'.
Keywords: E37; E47; C22; C53; 330; Fed Greenbook; forecasting models; macroeconomic stability; predictive accuracy; sub-sample analysis; Wirtschaftsprognose; Prognoseverfahren; USA; Wirkungsanalyse; Gleichgewichtsmodell